Analysis of a Laxity Index Database and Comparison with the Fédération Cynologique Internationale Grades of This Population - Bertal, Mileva; Vezzoni, Aldo; Van der Vekens, Elke; Polis, Ingeborgh; Saunders, Jimmy H.; Broeckx, Bart J.G. (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Objective This study aimed to analyse the distribution of the laxity indices (LI) in a dog population, to compare the LI with the Fédération Cynologique Internationale (FCI) grades and to search for differences of LI between breeds.Study Design The database was composed of all dogs presented to the University Hospital of the Faculty of Veterinary Medicine in Ghent for obligatory hip screening between January 2016 and February 2019, and all patients presented to orthopaedic consultation between January 2017 and January 2019 for a complaint of hindlimb lameness, which underwent both a standard extended ventrodorsal radiograph of the hips and a stress radiograph revealing hip joint laxity. The latter was obtained by means of the Vezzoni-modified Badertscher distension device and the LI was calculated. For each dog of the population, the LI was then compared with the FCI grade.Results The LI values ranged between 0.15 and 1.04, with a mean of 0.46. The LI and the FCI grade increased together, and showed a moderate-to-good correlation. There was a highly significant overall difference in the mean value of LI per FCI grade group (p < 0.001). The mean LI of the Labrador Retrievers was slightly but significantly lower than the mean LI of the Golden Retrievers (p < 0.01).Conclusion The LI calculated on a stress radiograph taken with the Vezzoni-modified Badertscher distension device shows a good correlation with the FCI grade assigned on a standard extended ventrodorsal projection. A wide range of passive hip joint laxity exists in dogs considered to be phenotypically normal based on the FCI grading method.
Keywords: hip; laxity; database; stress; radiograph